Tekstualitas dan Kontekstualitas dalam Penafsiran serta Pengaruhnya bagi Kehidupan Sosial Masyarakat - Syifaudin Syifaudin (Journal of Innovative and Creativity, 2025)
The dynamics of Qur'anic exegesis have always been characterised by the tension between textualist and contextualist approaches. This study aims to analyse the fundamental characteristics of both approaches and to map their contrasting influences on contemporary social life in Indonesia. Employing a qualitative, library-based research design, primary and secondary data were analysed through hermeneutic and comparative approaches. The principal data sources include representative works of tafsīr (Qur'anic exegesis) from both schools of thought, supported by relevant academic journals, books, and articles. The findings indicate that the textualist approach tends to yield rigid and exclusive interpretations, which can potentially create social friction, particularly concerning issues of pluralism and gender equality. Conversely, the contextualist approach, which considers the maqāṣid al-sharī'ah (higher objectives of Islamic law) and modern social realities, tends to produce more dynamic, inclusive, and adaptive interpretations. In conclusion, the choice of interpretive methodology is not merely an academic debate but has direct implications for social harmony and justice within society. This study therefore recommends strengthening the discourse on contextual tafsīr within educational and religious institutions